Design of Continuum Robot with Variable Stiffness for Gastrointestinal Stenting Using Conformability Factor - 최준명; 안세혁; 김천우; 박정훈; 송호영; 조규진 (Institute of Electrical and Electronics Engineers Inc., 2020)
Stent placement in the gastrointestinal tract has emerged as an effective method of therapy for intestinal obstruction. In fluoroscopic guided stenting, clinicians first insert a hyper-elastic guidewire, and a stent introducer loaded with a compressed stent is passed along the guidewire to the desired deployment site. However, the high bending stiffness of the loaded stent introducer tends to straighten the inserted guidewire at the tortuous region. To overcome this issue, tubes of various stiffnesses are repeatedly inserted and removed. To optimize the mechanical properties of the devices for successful GI stenting, the interaction between the device and the environment should be considered as a key factor. In this study, conformability factor, a new index that abstracts the physical interaction for GI stenting was proposed. Based on the conformability factor, we proposed design requirements for variable stiffness continuum robots for GI stenting. The in vitro stent deployment experiment result shows that the proposed instrument can successfully deploy the loaded stent introducer without exchanging multiple tubes.